The Effectiveness of Transition Interventions to Support Older Patients From Hospital to Home: A Systematic Scoping Review. (November 2021) - O'Donnell, Renee; Savaglio, Melissa; Skouteris, Helen; Banaszak-Holl, Jane; Moranl, Chris; Morris, Heather; Vicary, Dave; Ayton, Darshini
Background: Interventions supporting older adults' transition from hospital to home can address geriatric needs. Yet this evidence base is fragmented. This review describes transitional interventions that provide pre- and post-discharge support for older adults and evaluates their implementation and effectiveness in improving health and well-being. Method: Articles were included if they examined the extent to which transitional interventions were effective in improving health and well-being outcomes and reducing hospital readmission rates among older adults. Results: Twenty studies met the inclusion criteria. Four types of interventions were identified: education-based (10/20); goal-oriented (4/20); exercise (4/20); and social support interventions (2/20). Education and goal-oriented interventions were effective in improving health and well-being outcomes. The impact of interventions on mitigating hospital readmissions was inconclusive. Only five studies examined implementation. Discussion: Older adults transitioning from hospital to home would benefit from tailored education and goal-oriented interventions that promote their capacity for self-care.